Long-term electricity demand forecast and supply side scenarios for Pakistan (2015–2050): A LEAP model application for policy analysis - Mirjat, N. H.; Uqaili, M. A.; Harijan , K.; Walasai, G. D.; Mondal, M.A.H.; Sahin, H. (Elsevier, 2018)
Pakistan is facing electricity crises owing to lack of integrated energy planning, reliance on imported fuels for power generation, and poor governance. This situation has challenged governments for over a decade to address these crises. However, despite various conformist planning and policy initiatives, the balance between demand and supply of electricity is yet to be achieved. In this study, Long-range Energy Alternatives Planning System (LEAP) is used to develop Pakistan's LEAP modeling framework for the period 2015–2050. Following demand forecast, four supply side scenarios; Reference (REF), Renewable Energy Technologies (RET), Clean Coal Maximum (CCM) and Energy Efficiency and Conservation (EEC) are enacted considering resource potential, techno-economic parameters, and CO2 emissions. The model results estimate the demand forecast of 1706.3 TWh in 2050, at an annual average growth rate of 8.35%, which is 19 times higher than the base year demand. On the supply side, RET scenario, although capital-intensive earlier in the modeling period, is found to be the sustainable electricity generation path followed by EEC scenario with the lower demand of 1373.2 TWh and minimum Net Present Value (NPV) at an aggregate discount rate of 6%. Conclusion section of the paper provides the recommendations devised from this study results.